Borders of Art in Ancient and Modern Material Culture - Butyagin, Alexander M. (Actual Problems of Theory and History of Art, 2019)
The article discusses the meaningful definition of the concept of art for objects of material culture and the possibility of its expansion to other kinds of art. Each subject might be considered as a complex of features, some of them may bear artistic values. It turns out that for art related features deviations from the cultural accepted standard are crucial. The object with a certain number of deviations from anticipated standard would be most likely perceived as an art object. Thus we assume that the field of art is on the one hand limited by the standard, on the other hand, by such degree of deviation that goes beyond the comprehension of an ordinary culture bearer. With some restrictions this principle can be extended to other areas of human activity.
Keywords: artifact; deviation; borders of art; material culture